The Role of School Principals in Enhancing Elementary School Graduate Quality: A Comparative Analysis in Cianjur - Nurhayani; Eva Dianawati Wasliman, (Journal of Science and Education (JSE), 2025)
This study investigates the strategies employed by school principals at SDN Panyindangan and SDN Kertajaya in Cianjur Regency to enhance the quality of elementary school graduates. Employing a qualitative case study approach, the research applies the Plan-Do-Check-Act (PDCA) framework to examine principals’ planning, implementation, evaluation, and follow-up actions. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings reveal that leadership strategies are strongly influenced by each school’s context, including available resources, teacher competencies, socio-economic conditions, and community engagement. SDN Panyindangan prioritized remedial programs, character and religious development, and parental involvement, while SDN Kertajaya emphasized curriculum innovation, digital literacy, and project-based learning. The systematic application of the PDCA cycle facilitated continuous improvement, while adaptive and collaborative solutions addressed challenges such as limited facilities and variable teacher skills. This study concludes that effective school leadership is context-sensitive and participatory, and that tailored, systematic, and adaptive strategies can significantly improve graduate quality. The results provide practical insights for school leaders, teachers, and policymakers seeking sustainable approaches to enhancing educational outcomes in diverse settings. This study investigates the strategies employed by school principals at SDN Panyindangan and SDN Kertajaya in Cianjur Regency to enhance the quality of elementary school graduates. Employing a qualitative case study approach, the research applies the Plan-Do-Check-Act (PDCA) framework to examine principals’ planning, implementation, evaluation, and follow-up actions. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using Miles and Huberman’s interactive model. The findings reveal that leadership strategies are strongly influenced by each school’s context, including available resources, teacher competencies, socio-economic conditions, and community engagement. SDN Panyindangan prioritized remedial programs, character and religious development, and parental involvement, while SDN Kertajaya emphasized curriculum innovation, digital literacy, and project-based learning. The systematic application of the PDCA cycle facilitated continuous improvement, while adaptive and collaborative solutions addressed challenges such as limited facilities and variable teacher skills. This study concludes that effective school leadership is context-sensitive and participatory, and that tailored, systematic, and adaptive strategies can significantly improve graduate quality. The results provide practical insights for school leaders, teachers, and policymakers seeking sustainable approaches to enhancing educational outcomes in diverse settings.